PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN MEDIASI WORKPLACE SPIRITUALITY - Tri Suwarni (2024)
Each employee's performance will be given a different portion of work, which reflects the use of productive work time within a certain period of time. However, the use of time at work is often employees get an excessive workload, making it uncomfortable for employees who can cause fatigue. OCB behavior, contributions that exceed the job description, critical to achieving company goals are positive actions of employees in the organization. The results of the 2021 industry research show that most workers have low OCB, caused by exhausting workload and lack of cooperation. This study aims to analyze workload and work environment on OCB with Workplace Spirituality mediation. The sample of respondents in this study were 173 employees at the Center for Safety of Medical Devices and Facilities (BPAFK) through electronic questionnaires and using quantitative methods with descriptive data analysis techniques using smartPLS. This study shows that workload and work environment affect (OCB) there is a significant effect on the effect of workload and work environment on OCB with Workplace Spirituality mediation. The value of the direct path coefficient of workload and work environment on OCB is greater when compared to the mediation of Workplace Spirituality, this may be a factor.